Dose-rate effects in radiation biology and radiation protection. (June 2016) - Rühm, W.; Azizova, T.V.; Bouffler, S.D.; Little, M.P.; Shore, R.E.; Walsh, L.; Woloschak, G.E.
Quantification of biological effects (cancer, other diseases, and cell damage) associated with exposure to ionising radiation has been a major issue for the International Commission on Radiological Protection (ICRP) since its foundation in 1928. While there is a wealth of information on the effects on human health for whole-body doses above approximately 100 mGy, the effects associated with doses below 100 mGy are still being investigated and debated intensively. The current radiological protection approach, proposed by ICRP for workers and the public, is largely based on risks obtained from high-dose and high-dose-rate studies, such as the Japanese Life Span Study on atomic bomb survivors. The risk coefficients obtained from these studies can be reduced by the dose and dose-rate effectiveness factor (DDREF) to account for the assumed lower effectiveness of low-dose and low-dose-rate exposures. The 2007 ICRP Recommendations continue to propose a value of 2 for DDREF, while other international organisations suggest either application of different values or abandonment of the factor. This paper summarises the current status of discussions, and highlights issues that are relevant to reassessing the magnitude and application of DDREF.